2020
DOI: 10.1002/advs.202002221
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Profiling of Engineered Nanomaterials: Unmasking the Surface Coating Effect

Abstract: Despite considerable efforts, the properties that drive the cytotoxicity of engineered nanomaterials (ENMs) remain poorly understood. Here, the authors inverstigate a panel of 31 ENMs with different core chemistries and a variety of surface modifications using conventional in vitro assays coupled with omics-based approaches. Cytotoxicity screening and multiplex-based cytokine profiling reveals a good concordance between primary human monocyte-derived macrophages and the human monocyte-like cell line THP-1. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…A lncRNA-gene co-expression network analyses based on Pearson’s correlation coefficient, R > 0.8 to at least 15 genes, identified a set of 242 lncRNAs, whose relative expression profiles separate the exposed mice into 4 categories of unexposed, low, medium, and high relative toxicities. This ranking is consistent with in vitro cytotoxicity of the same materials in human primary macrophages and a THP-1 cell line [ 15 ]. These 242 lncRNAs were upregulated relative to control exposures and were highly associated with genes involved in regulation of cell cycle, chromosomal organization, and DNA damage response ( Figure 4 , right panel), suggesting these are shared mechanisms that explain the relative cytotoxicity of these set of ENM.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A lncRNA-gene co-expression network analyses based on Pearson’s correlation coefficient, R > 0.8 to at least 15 genes, identified a set of 242 lncRNAs, whose relative expression profiles separate the exposed mice into 4 categories of unexposed, low, medium, and high relative toxicities. This ranking is consistent with in vitro cytotoxicity of the same materials in human primary macrophages and a THP-1 cell line [ 15 ]. These 242 lncRNAs were upregulated relative to control exposures and were highly associated with genes involved in regulation of cell cycle, chromosomal organization, and DNA damage response ( Figure 4 , right panel), suggesting these are shared mechanisms that explain the relative cytotoxicity of these set of ENM.…”
Section: Discussionsupporting
confidence: 81%
“…All 16 engineered nanomaterials studied were provided by the FP7-NANOSOLUTIONS consortium. Their synthesis, functionalization, and characterization are extensively described elsewhere [ 6 , 14 , 15 ]. Following the NANOSOLUTIONS standard operating procedures provided for each material, endotoxin free water (HyClone, HyPure Cell Culture Grade Water, Thermo Scientific, Waltham, MA, USA) was used for all ENM dispersions in glass tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on the synthesis can be found in ref. 14 . Moreover, the Expanded Methods in the Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Hufnagel et al [ 20 ] applied an RT-PCR based array spanning 95 genes and found that HMOX1 as well as HSPA1A (encoding heat shock 70 kDa protein 1, also known as HSP72) were both upregulated in A549 cells exposed to CuO NPs. It also deserves mentioning that we recently performed a transcriptomics study of THP-1 cells exposed to a panel of 31 nanomaterials including pristine CuO NPs at a low dose, corresponding to a maximum of 10–15% cell death (EC 10 ) for 24 h [ 83 ], and we found that the most upregulated gene in cells exposed to CuO NPs was HMOX1 encoding HO-1. Furthermore, 10 of the 20 most upregulated genes encoded different MTs.…”
Section: Discussionmentioning
confidence: 99%